Diffuse Large B-Cell Lymphoma Complicated by Small Bowel Obstruction after Radiotherapy: a Case Study - Diah Ari Safitri; Kartika Widayati Taroeno-Hariadi; Johan Kurnianda; Ibnu Purwanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTAlthough the spleen is frequently involved in disseminated non-Hodgkin’s lymphoma (NHL), splenic presentation as the initial or only site of disease is uncommon. Treatment modalities include surgery, chemotherapy, and radiation therapy. The priority of cancer follow up is to perform surveillance for recurrent cancer and evaluation of treatment response. Side effects of treatment are frequently missed or overlooked. A 66-year-old woman was presented to our hospital with a month history of spleen enlargement. On physical examination the spleen was palpated at Schuffner 2. Abdominal MSCT scan was suggestive of lymphoma. Surgery revealed adhesion and obstruction of the stomach. Biopsy and gastrojejunostomy shunting were done, but splenectomy was difficult. The pathology anatomy findings confirmed the diagnosis of diffuse non Hodgkin’s lymphoma large B-cell type. Immunohistochemistry showed positive CD3 and CD20. She underwent 6 cycles of rituximab, cyclophosphamide, adriamycin, vincristine, and prednisolone (RCHOP) chemotherapy. CT evaluation done 7 months later revealed that the hilus lienalis lymph nodes and spleen has decrease in size. However, a lumbosacral x-ray done due to back pain revealed metastasis on her 1st and 2nd lumbal spine. After a single fraction of radiotherapy, nausea, vomiting and abdominal distension occurred. A 3 position abdominal x-ray revealed signs of small bowel obstruction. After surgery she has received 9 cycles of zoledronic acid and remained in good condition and ambulatory. Splenic presentation as the initial or only site of non-Hodgkin’s lymphoma (NHL) is uncommon. Acute small bowel obstruction and fistula due to palliative radiation therapy for bone metastasis needs prompt and appropriate treatment.